SGTx1‚ a Kv channel gating−modifier toxin‚ binds to the interfacial region of lipid bilayers - Wee, C; Bemporad, D; Sands, Z; Gavaghan, D; Sansom, M (2007)
SGTx1 is a gating-modifier toxin that has been shown to inhibit the voltage-gated potassium channel Kv2.1. SGTx1 is thought to bind to the S3b-S4a region of the voltage-sensor, and is believed to alter the energetics of gating. Gating-modifier toxins such as SGTx1 are of interest as they can be used to probe the structure and dynamics of their target channels. Although there are experimental data for SGTx1, its interaction with lipid bilayer membranes remains to be characterized. We